العربيةُ الفصحى وأبرزُ التحدِّياتِ المعاصرةِ التي تواجهُها: challenges, Modern Standard Arabic, social media - al-Haddad, Abdulwahab Abdulaziz Kassem; Pa, Mat Taib (Al-Ḍād Journal, 2019)
These days, Arabic language is facing several of serious challenges which affected negatively on writing and pronunciation. Come on the top is a lot of new vocabulary that modern social media have added to classic Arabic language. However, these vocabulary do not belong to classical Arabic or even to any of its accents. Slowly, these vocabulary began controlling the imposition on social media, which requires facing these challenges on more than one level. This topic will be discussed through this study,in both side theoretical and field,to identify the most important contemporary challenges and their nature and how to confront it.